PENGGUNAAN VIDEO PEMBELAJARAN BUATAN GURU BERBASIS GOOGLE CLASSROOM PADA MATERI TRIGONOMETRI - Emilia Winda Sinom; Bistari Bistari; Silvia Sayu (Universitas Tanjungpura, 2021)
AbstractThe aims of this research are to determine and decribe the use of teacher-madelearning videos on trigonometry material. This research was conducted in classx science 1 and x science 2 at SMAN 10 Pontianak. In doing the reseacrh thewriter used descriptive qualitative method. The techniques of data collectionsthat used in this research were interviews, observation, and written tests. Thetechnical analysis of data in this research is to reduce the data that has beenobtained, present the data, and draw the conclusions. The subject in thisresearch was a teacher and 63 students. The results of this analysis showed thatthe use of learning videos is still not optimal. In making learning videos, thereare 3 stages namely preparation, manufacturing process, and finalmanufacture. While in the learning process there are still many students whoare less active and in the 2013 curriculum students are required to be active.As well as on student learning outcomes show that there are still some studentswho have not completed, which is around 31.7%.Keywords: Use Of Learning Videos, Teacher-Made, Trigonometry Material.